MRI findings of orbicularis oculi hypertrophy due to heavy resistance training on the inferior orbital rim - Abu Hassan, Hasyma; Mohd Ramli, Norlisah; Choong, Kenneth Sian Fong; Goh, Khean Jin (ASEAN Neurological Association, 2013)
Increase in cross-sectional muscle area of major muscle groups associated by heavy resistance training has been well documented. However, there has been no published article of changes in the inferior orbicularis oculi muscle when heavy resistance training is applied. We present a case of inferior orbicularis hypertrophy detected on MRI in a gentleman who practised heavy resistance training using his lower eyelids.